Preparation of ceramic support coating by using tin octoate: the effect of tin octoate concentration: article - Mohd Adnan, Nurasmida; Ibrahim, Norliza (2018)
Ceramic support coating by using tin octoate is used in the production of polylactic acid (PLA). The problem is when the concentration of the coating is thick, the shrinkage and cracking of the coating will occur. Therefore, a homogenous solution consists of tin octoate need to be achieved as to get a good attachment on ceramic support so that no shrinkage will occur. In order to get a homogenous solution, a specified concentration of tin octoate in ceramic support coating is needed. Hence, several concentrations of tin octoate are prepared as different concentration will give different effect on the coating. The purpose of the research is to investigate the immobilization of the catalyst (tin octoate) and the effect of different concentrations of tin octoate on the ceramic support. It is also to analyse the adhesion and characteristic of coating using adhesion test and emission dispersion x-ray spectroscopy (EDX). In this experiment, the ceramic support and 250 ppm, 500 ppm, 750 ppm of tin octoate solution need to be prepared. Then, the ceramic support is coated with tin octoate solution and the investigation on the coating characteristic is done by using adhesion test and EDX. The result is then analysed and it is observed that ceramic support coated with 500 ppm of tin octoate solution has the highest distribution of tin and has the strongest adhesion compared to ceramic support coated with 250 ppm and 750 ppm of tin octoate solution.